2017
DOI: 10.1080/21681805.2016.1271353
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic drug use and prostate cancer risk in the Finnish Randomized Study of Screening for Prostate Cancer

Abstract: Among antidiabetic drug users, metformin lowered the overall PCa risk, while the risk of metastatic disease was elevated in sulphonylurea users. As sulphonylureas stimulate insulin secretion, the results suggest that hyperinsulinemia may be a risk factor for PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 31 publications
3
42
0
Order By: Relevance
“…While exact mechanisms behind this remain unclear, some hypothesized that it is linked to Metformin's inhibitory effects on cancer cell proliferation pathways [27]. Haring et al [28] and Häggström et al [29] independently conducted nationwide cohort studies to evaluate the risk of PCa among users of Metformin.…”
Section: Anti-diabetic Drugs (Metformin)mentioning
confidence: 99%
See 2 more Smart Citations
“…While exact mechanisms behind this remain unclear, some hypothesized that it is linked to Metformin's inhibitory effects on cancer cell proliferation pathways [27]. Haring et al [28] and Häggström et al [29] independently conducted nationwide cohort studies to evaluate the risk of PCa among users of Metformin.…”
Section: Anti-diabetic Drugs (Metformin)mentioning
confidence: 99%
“…They first confirmed an inverse relationship between T2DM and PCa risk by comparing anti-diabetic drug users (n = 15,578) to non-users (n = 63,037). Specific effects of Metformin were then investigated through comparing the PCa risk between users of Metformin and other oral anti-diabetic drugs [28]. Due to the retrospective nature of the study, confounding covariates that may have influenced the results could not be controlled.…”
Section: Anti-diabetic Drugs (Metformin)mentioning
confidence: 99%
See 1 more Smart Citation
“…17 Importantly, there is evidence to show that the use of the antidiabetic drug metformin has a protective effect against cancer in general, but particularly against endometrial and prostate cancers. 18,19 A recent in vitro study showed that metformin can decrease cell survival by decreasing ROS production, partly through downregulation of NOX4 protein expression. 20 Moreover, NOX4 is involved in the inhibition of insulin signaling by inhibiting the phosphorylation of the insulin receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of the mammalian target of rapamycin (mTOR) (18)(19)(20)(21) and of cyclin D1 contributes to the anti-cancer effect of MET (18). A recent epidemiological study has demonstrated that overall PCa risk decreases in diabetic patients treated with MET (HR=1.44, 95% CI=1.09-1.91) (22), while a single-arm phase II clinical trial has found that MET can delay the progression of metastatic PCa, as measured by prostate-specific antigen (PSA) doubling time (23). However important these findings may be, they have been obtained after only a short period of treatment with no control arm included in the studies.…”
mentioning
confidence: 99%